PENGARUH TEKNIK PEMASANGAN SCOT MATA TERHADAP HASIL AKHIR RIASAN MATA (EYE MAKEUP) PADA MODEL BERMATA MONOLID - Nur Hermawan, Aulia; Salwa Evelyna, Aida; Rizqia Ardana, Arvy; Ratna Dita, Silfa; Vika Aulia, Fadila; Maghfiroh, Anik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Eyes are a crucial element in facial aesthetics, serving as the center of visual attention. For individuals with narrow or monolid eyes, eye shape correction is often necessary to achieve a more proportional appearance. This study aims to analyze the visual transformation of monolid eyes before and after the use of scotch tape. Using qualitative methods through a literature review of various credible articles, the study results indicate that scotch tape is an effective correction technique for maximizing eye dimensions. This study concludes that the use of scotch tape is the most efficient, safe, and instant non-surgical solution for providing visual correction.